2018
DOI: 10.1080/2156857x.2018.1538897
|View full text |Cite
|
Sign up to set email alerts
|

Professionalised, hybrid, and layperson models in Nordic child protection - actors in decision-making in out of home placements

Abstract: Decisions about child protection and interventions in families are one of the most difficult responsibilities of welfare states. The aim of this article is to describe and analyse the commonalities and differences in the child protection decision-making systems in Sweden, Norway, Finland, and Denmark. We focus on the actors involved, especially the laypersons, and their role in the decision-making process when deciding on out-ofhome placements, both on voluntary and coercive grounds.The study is based on a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…In the context of the COVID-19 pandemic lockdown, Bérubé et al ( 2020 ) argued that supportive systems, including healthcare and CPS, could not meet the needs of children due to the closing of schools and childcare centres. Several studies (Toros and Falch-Eriksen 2020 ; Jentsch and Schnock 2020 ) found that one of the challenges of COVID-19 for CPS was the loss of collaboration opportunities with key partners, including nursery schools. Jentsch and Schnock ( 2020 ) reported that the lockdown did not support the reporting process.…”
Section: Concluding Thoughtsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of the COVID-19 pandemic lockdown, Bérubé et al ( 2020 ) argued that supportive systems, including healthcare and CPS, could not meet the needs of children due to the closing of schools and childcare centres. Several studies (Toros and Falch-Eriksen 2020 ; Jentsch and Schnock 2020 ) found that one of the challenges of COVID-19 for CPS was the loss of collaboration opportunities with key partners, including nursery schools. Jentsch and Schnock ( 2020 ) reported that the lockdown did not support the reporting process.…”
Section: Concluding Thoughtsmentioning
confidence: 99%
“…Several studies (Toros and Falch-Eriksen 2020 ; Jentsch and Schnock 2020 ) found that one of the challenges of COVID-19 for CPS was the loss of collaboration opportunities with key partners, including nursery schools. Jentsch and Schnock ( 2020 ) reported that the lockdown did not support the reporting process. Similarly, Turner ( 2020 ) addressed limited collaboration from key partners due to COVID-19.…”
Section: Concluding Thoughtsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is very different from adversarial child welfare decision-making systems, with courts as the main decision-making bodies, as highlighted in several Anglo-American studies (e.g., Burns et al, 2017). The Finnish system also stands out from the other Nordic countries with its emphasis on child welfare professionals making the majority of the removal decisions (Hultman et al, 2018). The practice obviously gives a lot of power to social workers but also to parents and children (of certain ages): they are given the power to say that the child can be taken into public care without court involvement.…”
Section: Giving Consent In Care Order Decision-makingmentioning
confidence: 99%
“…For a more comprehensive description of the Swedish decision‐making system, see, for example, Hultman, Forkby, and Höjer, ()…”
mentioning
confidence: 99%